REALITAS SEJARAH DAN KELAS SOSIAL DALAM NOVEL NAMAKU ALAM KARYA LEILA S. CHUDORI - Mayangsari, Nadya; Rachmawati, Kurnia; Susanto, Arju (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the historical reality and social class in the novel Namaku Alam by Leila S. Chudori using materialism theory and Karl Marx's social class theory. The type of research is qualitative descriptive research. Data collection techniques are used by reading, recording, and conducting literature studies. The data analysis technique in this research is descriptive analysis. The results of this study found the existence of historical realities that occurred in 1965 and the existence of social conflicts, which are divided into four social class data sets. The upper class is described as the Sastrowidjojo family, who live in Papandayan, Bogor, and have the power to oppress the lower class. The lower class was found to be poor and weak. The transfer of power from the ruling class to another class that has more advanced thinking for the next generation is referred to as a revolution. Ideology is found in teachings that describe a situation with the intention of deceiving the opposing party, which in essence only supports the class that has power.